Pengaruh Homesickness Akut Terhadap Proses Adaptasi Dunia Perkuliahan Mahasiswa Baru Rantau - Sri Suryani Mimah; Oktaviani Adhi Suciptaningsih (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Education is a process where individuals acquire knowledge and skills as provisions to be able to participate in the welfare of society. There are many things you can do to get a decent education, one of which is going to study in a new country (region). A person who is studying at university or college level is called a student. Students who are studying at a university and decide to leave their home and place of origin are called 'Overseas Students'. In their first year of study, overseas students will experience homesickness or an excessive feeling of longing for home. This homesickness phenomenon also occurs in new overseas students at the State University of Malang. From the results of research conducted by researchers, the percentage of homesickness experienced by Malang State University students reached 58%. This research was carried out using a quantitative survey method in the form of filling out questionnaires at several faculties at the State University of Malang. The data obtained was that 42 students experienced homesickness, 20 students often experienced homesickness, and 11 students rarely experienced homesickness. With the percentage figures obtained, of course homesickness is something that must be paid attention to, even though in quotes homesickness is not a mental illness, the consequences of homesickness itself can disrupt mental health. Of course, there are many ways you can reduce homesickness, such as doing useful activities. Homesickness cannot be cured completely, because basically longing is something that remains in the human conscience. However, homesickness can be overcome by finding a comfortable environment.